Effect of Conservation Tillage and Integrated Weed Management on Yield, Energy Consumption and Profitability of Wheat in Khuzestan - Rahim NorAftab (University of Tabriz, 2021)
Abstract Background and Objective: The aim of this study was to investigate the effects of tillage and integrated weed management on growth, yield, yield components, resource use efficiency and inputs such as energy and herbicides in wheat.